The Use of Sports Broadcasting in Developing Knowledge about Sports in Indonesia - Haris Pramajakti; Darryl Valerian Pramudita; Romeo Matthew Alexandro Pantouw; Niken Febrina Ernungtyas (Eduvest - Journal of Universal Studies, 2025)
The development of digital communication technology today has had a significant impact on various aspects of life, including the development of sports knowledge. Sports broadcast media, whether through television, radio, podcasts, vodcasts, or social media platforms, play an important role in disseminating information about sports. This research aims to explore how various forms of sports broadcast media contribute to enriching the audience's understanding of sports, both in terms of technique, history, and match analysis. Using the Systematic Literature Review (SLR) approach, this study analyzed the existing literature to identify the main themes that emerged in previous research and evaluate the impact of these media on increased knowledge and audience engagement. The results show that sports broadcast media can increase active participation of fans through interactivity and flexible content access, with new technologies such as Augmented Reality (AR) and artificial intelligence (AI) further enriching the viewing experience. This study concludes that sports broadcast media not only serves as a means of entertainment, but also as an effective educational tool to increase the knowledge and involvement of audiences in the world of sports.